2022
DOI: 10.3390/ijms231911906
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian Randomization Studies of Lifestyle-Related Risk Factors for Osteoarthritis: A PRISMA Review and Meta-Analysis

Abstract: Risk factors for osteoarthritis (OA) often exert effects over protracted time-courses. Mendelian randomization (MR) studies therefore have an advantage over conventional observational studies when studying the causal effect of long-term lifestyle-related risk factors on OA. However, given the heterogeneous design of existing MR studies on OA, the reported causal estimates of these effects remain inconsistent, thus obscuring the true extent of the biological effects of OA lifestyle-risk factors. We conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…In individuals with high BMI, the load-bearing pressure on the hip and knee joints is greater than that in normal-weight individuals, leading to increased friction between the articular cartilage and facilitating the development of knee and hip OA. Earlier studies have also demonstrated a link between elevated BMI and the progression of arthritis [ 29 , 30 , 43 ]. However, even after accounting for BMI as an intermediate variable, the effects of total statins and simvastatin on hip OA remained significant.…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with high BMI, the load-bearing pressure on the hip and knee joints is greater than that in normal-weight individuals, leading to increased friction between the articular cartilage and facilitating the development of knee and hip OA. Earlier studies have also demonstrated a link between elevated BMI and the progression of arthritis [ 29 , 30 , 43 ]. However, even after accounting for BMI as an intermediate variable, the effects of total statins and simvastatin on hip OA remained significant.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis may seem to be inevitable with increased age [ 33 ]; it can be halted and/or postponed with the adoption of the previously mentioned lifestyle changes. These interventions are most effective if they are implemented in the early years of childhood [ 34 ]. Period effect refers to the improvement of public health intervention measures, health education policies, and treatment methods in a certain period, which will have an impact on the period effect of onset and death of osteoarthritis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the data used in this study were from populations of European ancestry, which does not reflect the heterogeneity among different populations. Third, as MR analysis assesses the cumulative effects of genetic variation, we cannot extrapolate the possible effects of clinical treatment [ 48 ]. In addition, there may be time-dependent effects and inflammation-environment interactions that could influence the results of our analysis.…”
Section: Discussionmentioning
confidence: 99%